Peran Direktorat Kepolisian Perairan dan Udara Polda Aceh dalam Penanggulangan Narkotika di Wilayah Perairan Aceh - Depita Kardiati (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The circulation of narcotics in Aceh's territorial waters is a serious problem that affects the security and welfare of the community. This research aims to analyze the role of the Directorate of Water and Air Police (DITPOLAIRUD) of the Aceh Regional Police in efforts to control narcotics through preventive and repressive measures. The research method uses a descriptive qualitative approach with data collection techniques through interviews, literature studies and document analysis. The research results show that Ditpolairud's preventive actions include routine patrols in water areas, strict monitoring of smuggling-prone routes, as well as quick response through a quick response system. However, the implementation of this action is hampered by limited resources, such as patrol boats, ship detection technology and integrated hotlines. Meanwhile, repressive measures include arresting perpetrators, investigating and compiling case files which also face challenges in terms of the availability of personnel and forensic facilities. This research concludes that optimizing the role of the Aceh Regional Police's Ditpolairud requires increased support for facilities, infrastructure and personnel training to maximize the effectiveness of countering narcotics in Aceh's territorial waters.